1994
DOI: 10.1038/npp.1994.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clozapine Treatment on Serotonin-2—Receptor Binding in the Blood Platelets of Schizophrenic Patients

Abstract: The effect of clozapine and typical neuroleptic drug treatment on platelet serotonim (5-HT2) binding kinetic constants (Kd, Bmax) was studied in schizophrenic patients. Both treatments increased Bmax by a comparable amount, indicating increased numbers of 5-HT2 sites, although not all typical neuroleptic drugs were effective in this regard. Clozapine, but not typical neuroleptic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…A few studies of platelet 5‐HT 2A receptors in suicidal patients have found increased platelet 5‐HT 2A receptors in suicidally depressed but not nonsuicidally depressed patients. Further, our studies 21 and the studies of Arora and Meltzer 25 indicate that platelet 5‐HT 2A receptors may be increased in suicidal patients independent of diagnosis. In summary, these studies indicate that platelet 5‐HT 2A receptors are increased in depression, that this increase may be related to suicidal behavior, and that the increase in platelet 5‐HT 2A receptors in suicidal patients appears to be independent of diagnosis and may be state related.…”
Section: Serotonin Studies In Plateletssupporting
confidence: 56%
See 2 more Smart Citations
“…A few studies of platelet 5‐HT 2A receptors in suicidal patients have found increased platelet 5‐HT 2A receptors in suicidally depressed but not nonsuicidally depressed patients. Further, our studies 21 and the studies of Arora and Meltzer 25 indicate that platelet 5‐HT 2A receptors may be increased in suicidal patients independent of diagnosis. In summary, these studies indicate that platelet 5‐HT 2A receptors are increased in depression, that this increase may be related to suicidal behavior, and that the increase in platelet 5‐HT 2A receptors in suicidal patients appears to be independent of diagnosis and may be state related.…”
Section: Serotonin Studies In Plateletssupporting
confidence: 56%
“…did not find significant increases in suicidal patients, they reported that B max correlated with the medical damage of the suicide attempt. Arora and Meltzer 25 studied 5‐HT 2A receptors in schizophrenic and suicidal schizophrenic patients and reported an increase in suicidal schizophrenic patients compared to the control group.…”
Section: Serotonin Studies In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 125 I-LSD, B max values of platelet 5HT 2 receptors were shown to be higher in schizophrenic patients than controls (Pandey et al, 1993). These ®ndings could not be replicated once the statistical corrections for platelet as a psychiatric illnessage and sex effects were made (Arora and Meltzer, 1993). Marazziti et al (1989) …”
Section: Platelet Receptor Studiesmentioning
confidence: 94%
“…The direction of findings in the brain of suicides is consistent with some platelet findings in suicide attempters. For example, more platelet 5-HT 2A receptors are found in suicide attempters compared with non-attempters and healthy controls (Arora and Meltzer, 1993 ;Biegon et al, 1990 ;McBride et al, 1994 ;Pandey et al, 1990Pandey et al, , 1995Rao et al, 1998), and in individuals with suicidal ideation compared to non-suicidal psychiatric patients and controls (Alda and Hrdina, 2000 ;Bakish et al, 1997 ;Hrdina et al, 1997). Two studies observed no difference (Serres et al, 1999 ;Uchitomi et al, 2002).…”
Section: Introductionmentioning
confidence: 92%